Activity of ethanol extracts of seledri (Apium graveolens) herbs and urang aring (Eclipta prostata (L.)L.) leaves against Pityrosporum ovale - Elin Yulinah Sukandar; Suwendar .; Ernita Ekawati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Seledri (Apium graveolens) and urang aring (Eclipta prostata (L.)L.) have been used traditionally for hair grow. In this study, we want to test wether the both substances have an activity against Pityrosporum ovale as fungi causing dandruff. Anti Pityrosporum ovale activity of ethanol extracts of seledri (Apium graveolens) herbs and urang aring (Eclipta prostata (L.)L.) leaves had been studied using agar diffusion and dilution methods. Anti Pityrosporum ovale activity was shown by both of the two extracts, but seledri herbs extract showed stronger effect with inhibition diameter of as large as 16.33 ± 2.08 at the concentration of 5% w/v whereas that of urang aring leaves showed the inhibition diameter of 12.67 ±1.15 at the same concentration using agar difusion method. With agar dilution method, both of the two extracts still showed the inhibitory effects at the concentration of as low as 0.11 mg/mL.Key words : antifungi, Pityrosporum ovale, seledri, urang aring